Entre o empoderamento e a precariedade: o empreendedorismo feminino no setor de vendas diretas de cosméticos - Silva, Mayco Lima da (2023)
After the year 1970 a variety of transformations have occurred in our society and in the labor world that have marked the beginning of the flexible period of capitalist accumulation. Those transformations represent a significant increase of labor precarity throughout the labor flexibilization process. This process was accompanied by the increase of the services sector and by the increase of female participation at the labor force. In this context, entrepreneurship spreads as an alternative. From the work of cosmetics resellers of Mary Kay’s company that lives in Rio Grande do Sul and also from the management literature, the present research analyzes the relation between entrepreneurship, flexibility and informality. The aim is to comprehend in what level the female entrepreneurship inserts itself at the frontier between the empowerment and/or precarity, and analyze the reproduction of inequalities and/or possibilities of emancipation of this type of labor. From the interviews and the documentary research, the present work aims to comprehend the aspects of the Mary Kay’s consultants work, by investigating its self-definition as female entrepreneurship. The work analyzes how entrepreneurship and the spaces it occupies configures the reproduction of gender inequalities and/or female emancipation.